2022
DOI: 10.1007/jhep08(2022)053
|View full text |Cite
|
Sign up to set email alerts
|

Non-invertible symmetries of $$ \mathcal{N} $$ = 4 SYM and twisted compactification

Abstract: Non-invertible symmetries have recently been understood to provide interesting constraints on RG flows of QFTs. In this work, we show how non-invertible symmetries can also be used to generate entirely new RG flows, by means of so-called non-invertible twisted compactification. We illustrate the idea in the example of twisted compactifications of 4d $$ \mathcal{N} $$ N = 4 super-Yang-Mills (SYM) to three dimensions. After giving a catalogue of non-invertible symmetries descen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 49 publications
2
26
0
Order By: Relevance
“…[ 5–8 ] A number of recent works have shown that symmetry operators without inverses (and which are therefore not elements of any group, but should rather be thought of in categorical terms) are also very common in higher dimensional theories. [ 9–26 ] In this paper we will focus on one class of theories where such non‐invertible symmetries appear: scriptN=4$\mathcal {N}=4$ theories with gauge group Pin+(4N)$\mathrm{Pin}^+(4N)$, Scfalse(4Nfalse)$Sc(4N)$ and POfalse(4Nfalse)$PO(4N)$. [ 14 ] The details are a little different in the three cases, so in this introduction we will focus on the Scfalse(4Nfalse)$Sc(4N)$ case for concreteness.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5–8 ] A number of recent works have shown that symmetry operators without inverses (and which are therefore not elements of any group, but should rather be thought of in categorical terms) are also very common in higher dimensional theories. [ 9–26 ] In this paper we will focus on one class of theories where such non‐invertible symmetries appear: scriptN=4$\mathcal {N}=4$ theories with gauge group Pin+(4N)$\mathrm{Pin}^+(4N)$, Scfalse(4Nfalse)$Sc(4N)$ and POfalse(4Nfalse)$PO(4N)$. [ 14 ] The details are a little different in the three cases, so in this introduction we will focus on the Scfalse(4Nfalse)$Sc(4N)$ case for concreteness.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases we can see from the index of the resulting theory that the additional gauging of a zero-form symmetry is obstructed, thus indicating the presence of the mixed anomaly in the original theory. As it was pointed out in [37,43,45], if the resulting anomaly takes a suitable form, then it leads to interesting consequences after gauging. In particular, if we gauge the two zero-form symmetries in the original theory, the remaining one-form symmetry is noninvertible.…”
Section: Introductionmentioning
confidence: 86%
“…[ 5–7 ] The full physical impact of these symmetries is yet to be uncovered, but already numerous phenomenological and other applications have been studied. [ 8–13 ]…”
Section: Introductionmentioning
confidence: 99%